ANALISIS MEKANISME CORPORATE GOVERNANCE TERHADAP PROBABILITAS TERJADINYA EARNINGS RESTATEMENT - Bayu Indra Kusuma; Abdul Rohman (Diponegoro Journal of Accounting, 2014)
This paper seeks to examine the impacts of corporate governance on earnings restatement are indicated as a form of financial reporting failures on non-financial listed companies in Indonesia, with a view to providing reference to strengthen the corporate governance and improve the quality of financial information.            Data for this paper were obtained from the annual reports of non-financial listed companies from the period of 2004 to 2010 with a total population of 2.146, which includes 34 restatements especially earnings restatement by 34 companies. A control sample comprising non-restating companies is formed using match-pair procedures where restated and non-restated companies are matched by fiscal year, industry sector, and company size. Logistic regression model was used to measure the restatements dummy variables. Moreover, dummy variables are also used not only on the composition of the board and the concentration of ownership, but also the quality of the independent auditor. Earnings restatement on this paper focused on accounting misstatements and changes in accounting policies.            The results show that occurence of restatements especially earnings restatement can be prevented by strong internal governance, such as the proportion of independent directors and the ownership of large shareholders are higher. They have better control than others to monitoring and finding acts of fraud committed by management quickly and accurately. Surprisingly, the independence of the audit committee actually found a positive but not significant effect on the likelihood of higher restatements. The audit that have done by Big 4 found a negative but not significant effect on the likelihood of restatements is lower. While the government ownership found a positive but not significant effect on high possibility of restatements.